AGE-RELATED NORMS OF THE DEVELOPMENT OF BALANCE FUNCTION IN CHILDREN AGED 9-10 YEARS - L.Z. Kholmurodov (Research Focus International Scientific Journal, 2024)
The article presents a discussion of the conducted pedagogical experience in the use of physical education tools and their results, taking into account age-specific features in the development of balancing function in children aged 9-10 years in organizational learning.